2015
DOI: 10.1016/j.cell.2015.01.046
|View full text |Cite|
|
Sign up to set email alerts
|

COLD1 Confers Chilling Tolerance in Rice

Abstract: Rice is sensitive to cold and can be grown only in certain climate zones. Human selection of japonica rice has extended its growth zone to regions with lower temperature, while the molecular basis of this adaptation remains unknown. Here, we identify the quantitative trait locus COLD1 that confers chilling tolerance in japonica rice. Overexpression of COLD1(jap) significantly enhances chilling tolerance, whereas rice lines with deficiency or downregulation of COLD1(jap) are sensitive to cold. COLD1 encodes a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
608
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 738 publications
(667 citation statements)
references
References 68 publications
14
608
2
3
Order By: Relevance
“…Recently, Ma et al . 47 found that low temperature sensing in rice was related to changes in Ca 2+ influx during cold treatment, and the change in Ca 2+ influx was controlled by COLD1, a regulator of G‐protein signaling. In this study, the expression levels of HbCPK and HbCRK genes (Ca 2+ sensors) were examined under cold stress.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Ma et al . 47 found that low temperature sensing in rice was related to changes in Ca 2+ influx during cold treatment, and the change in Ca 2+ influx was controlled by COLD1, a regulator of G‐protein signaling. In this study, the expression levels of HbCPK and HbCRK genes (Ca 2+ sensors) were examined under cold stress.…”
Section: Resultsmentioning
confidence: 99%
“…2000; Ma et al. 2015). The first report about the importance of Ca 2+ as an important second messenger in animals was from the rapid cold‐hardening response in larvae of the Antarctic midge Belgica antarctica (Teets et al.…”
Section: Discussionmentioning
confidence: 99%
“…Low temperature is one of the most common environmental stress factors; it can affect rice architecture and seed germination, slow the growth rate, delay seed maturation, cause male sterility, decrease the seed setting rate, and ultimately reduce the rice yield (Fujino and Matsuda 2010;Fujino et al 2008;Ma et al 2015;Saito et al 2004Saito et al , 2010Suh et al 2010). Cold stress is a major factor contributing to reduced rice yield in temperate and high-altitude regions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, cold stress at the reproductive stage can negatively affect grain quality and production (Lee 2001;Xu et al 2008). Therefore, improving the cold tolerance of rice is an important objective in rice breeding, not only to maintain rice yields in cool regions, but also to expand the cultivation area of rice into northern areas or high-altitude regions with low temperatures (Ma et al 2015). Consequently, cold-tolerant rice cultivars would benefit grain production and contribute to food security and continuing development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation